Case Report: Masquerading doughnut: a case of misdiagnosed ileocecal tumor-induced intussusception - Xu, Chuchu; Zhu, Renjun; Dai, Qingfeng; Xu, Guangen; Zhang, Guolin (Frontiers in Oncology, 2025)
BackgroundIntussusception in adults is rare and is often associated with an underlying pathology such as tumors. Its coexistence with colorectal cancer (CRC) in young patients presents unique diagnostic challenges as imaging may suggest separate lesions rather than a single malignancy.Case presentationA 21-year-old man presented with worsening right upper and central abdominal pain. The contrast-enhanced abdominal CT suggested that the intussusception at the ileocecal region might be caused by a lipoma and revealed a separate mass in the transverse colon. Emergency laparoscopic exploration and subsequent open laparotomy confirmed a 4.0-cm × 5.0-cm cauliflower-like adenocarcinoma originating from the ileocecal region, which had caused the intussusception and mimicked separate pathologies on imaging.ConclusionsThis case highlights the diagnostic complexity of synchronous intestinal lesions in young patients. It underscores the need for a heightened suspicion of an underlying malignancy when encountering intussusception and emphasizes the limitations of imaging in accurately characterizing the complex pathology of the bowel.